Analysis of Ancient Indian Empires and Kingdoms: A Comparative Analysis of Ancient Indian Empires and Kingdoms (Journal of Advances and Scholarly Researches in Allied Education, 2018)
An empire is a political build where one state overwhelms over another state, or a progression of states. At its heart, a domain is administered by a sovereign, despite the fact that numerous states in history without a ruler at their head are designated empires.